What shall we do with the Canaanites?: an ethical perspective on Genesis 12:6 - Holter, Knut (Old Testament essays, 2017)
Colonial biblical interpretation-such as for example Moritz Merker's study of the Maasai (1904/1910), where he claims that they are historically related to the ancient Israelites-tend to see both "Israelites" and their counterparts, the "Canaanites," in the colonial, interpretive contexts. On this background, the present essay discusses a textual case, the reference to the Canaanites in Gen 12:6. It is suggested that the reference is part of a multi-voiced discourse on the role of the Canaanites, and it is concluded that the guild of biblical studies can use this discourse in relation to contemporary ethical and interpretive challenges.